Conveniencia de reconocer en la legislación Ecuatoriana la tenencia compartida, en aplicación del derecho constitucional del buen vivir y el principio de interes superior del menor - Corozo Diaz: Brigida Geovanka (2015)
The contemporary family is a social organization governed by a multitude of standards including economic, hygienic, aesthetic, religious, moral, political and legal, consisting of father, mother, children, and relatives, being the purposes as universal institution, strengthen the personality of the children in the psychological, moral, ethical, humane and training in their growth process. While it is true that in contemporary times, the Ecuadorian family is going through a critical stage, caused by several factors, both endogenous and exogenous harming directly and indirectly to the family way and particularly the younger. A problem arises when divorce occurs, the de facto union is terminated or are single mothers, the disintegration occurs, consequently the judge has to decide on food and tenure or minor under the rule of Article 108 of the Civil Code, which says, corresponds tenure: "1. A mother divorced or separated husband comes the care of prepubertal children, regardless of sex and daughters of all ages; and, 2. pubescent children are in the care of that parent they choose, "causing this legal provision discrimination from one to the other parent, limiting the right of access to care, parenting and child protection, recognizing and protecting unequal conditions of the two human beings who are their parents, without also observe the basic rights and guarantees of protection as a priority group and comprehensive care of the child, consequently, these considerations before our Ecuadorian law does not have clear rules and precise to allow, apply the principle of "equality" constitutional, that all persons are equal before the law and enjoy the same rights and opportunities, I think is paramount make my research regarding private law, family law in proportion to the need to recognize the shared ownership of the two parents, so that they can meet each and every one of the legal precepts in the child.